Population dynamics and structure of sperm whale (Physeter macrocephalus) in Mediterranean Sea - VIOLI, BIAGIO (Università degli studi di Genova, 2020)
The sperm whale (Physeter macrocephalus) has a cosmopolitan distribution. In the Mediterranean, sperm whale sub-population is classified as ‘Endangered’ according to the International Union for the Conservation of Nature. Even though this population hasn’t faced the whaling age, it is currently threatened by other anthropogenic impacts, which cause direct mortality and strandings (i.e. ship strikes, debris ingestion, entanglement in driftnets), or may cause indirect mortality (e.g. noise pollution). Previous genetic, acoustic and mark-recapture studies have indicated that this population is distinct from the North Atlantic population. Within the Mediterranean Sea, the population structure is however unclear. Photo-ID data have shown three recaptures between the eastern and the western basins, but no confirmation of breeding success between those basins is available to date. Genetic differentiation within the Mediterranean Sea has already been confirmed for various dolphin and fish species. Here, we investigate population structure and pattern of gene flow within the Mediterranean Sea, and between the Mediterranean and the close Atlantic area, using 11537 single nucleotides polymorphism sites (SNPs) generated by restriction-site-associated DNA sequencing (RADseq). We have sequenced 142 samples from stranded and free-ranging individuals, 104 samples from the Mediterranean Sea and 38 samples from the eastern North Atlantic. Results on genetic structure revealed, as suggested in previous studies, a division between Mediterranean and Atlantic areas. Through Gibraltar Straits gene flow rates are low but significant, revealing that some individuals cross the straits for breeding purposes. Within the Mediterranean, no division between western and eastern basins was found, confirming that Sicilian waters are not barriers to both movements and the gene flow. Furthermore, we found two different populations, a first one composed of samples from different areas of the Mediterranean basins, and a second one composed of ...